2016
DOI: 10.1186/s13054-016-1201-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of central venous catheter colonization using surveillance culture of withdrawn connectors and insertion site skin

Abstract: BackgroundCulture of catheter hubs and skin surrounding the catheter entry site has a negative predictive value for catheter tip colonization. However, manipulation of the hub for culture requires the hubs to be swabbed, introducing potential dislodging of biofilm and subsequent migration of microorganisms. Hubs are usually closed with needleless connectors (NCs), which are replaced regularly. Our objective was to evaluate whether culture of flushed withdrawn NCs is an alternative to hub culture when investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…10,11 Moreover recent studies have also shown the leading cause of CRBSI to be gram negative bacilli. 12 Acenitobacter baumannii was the most common organism isolated (29%) which is in contrast with the similar studies done in the past, [6][7][8][9][10][11] where some of the studies showed Staph. aureus, CONS and Pseudomonas aeruginosa as the commonest organism colonizing CVC.…”
Section: Escherichia Coli 1(5)mentioning
confidence: 60%
“…10,11 Moreover recent studies have also shown the leading cause of CRBSI to be gram negative bacilli. 12 Acenitobacter baumannii was the most common organism isolated (29%) which is in contrast with the similar studies done in the past, [6][7][8][9][10][11] where some of the studies showed Staph. aureus, CONS and Pseudomonas aeruginosa as the commonest organism colonizing CVC.…”
Section: Escherichia Coli 1(5)mentioning
confidence: 60%
“…Previous studies have been found that culture of skin insertion site had a good negative predicted valued for the prediction of the CRBSI or CVC tip colonization [ 9 16 ]. Novel aspects of our research were that we studied the capability of skin insertion site culture for predict CRBSI and PBSI.…”
Section: Discussionmentioning
confidence: 99%
“…The semiquantitative cultures of CVC insertion skin site is one of those conservative methods. Previous studies have analyzed the capability of skin insertion site culture to predict catheter-related bloodstream infection (CRBSI) or CVC tip colonization [ 9 16 ]. CRBSI has been defined in those studies as a positive blood culture by recognized pathogen, CVC tip colonization with the same microorganism, and no other apparent infection source.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was performed using two types of manipulation: 50 BCBs with NeutraClear® and 50 BCBs with MicroClave® manipulated following the standard of care under aseptic conditions (hand hygiene, sterile gloves, mask, and catheter hub disinfection by scrubbing three times with 70% alcohol before handling), and 50 BCBs with NeutraClear® and 50 BCBs with MicroClave® manipulated using contaminated gloves (impregnated in a 0.05 McFarland solution of Staphylococcus aureus ). The contaminated model was based on previous studies of our group which demonstrated that needleless connectors become contaminated after withdrawal with significant counts of bacteria and this could simulate what happens in the real clinical practice (1113).…”
Section: Methodsmentioning
confidence: 99%